Factors related to HIV testing frequency in MSM based on the 2011-2018 survey in Tianjin, China: a hint for risk reduction strategy - Zhongquan Liu; Yang Chen; Tingting Yao; Tiantian Zhang; Desheng Song; Yuanyuan Liu; Maohe Yu; Jie Xu; Zhijun Li; Jie Yang; Zhuang Cui; Changping Li; et al. (BMC, 2021)
Abstracts Background In recent years, HIV testing has become one of the effective strategies to reduce the risk of the infection. Frequent quarterly HIV testing can be cost effective. Therefore, an in-depth study of factors related to the testing behavior of men who have sex with men (MSM) were analyzed to optimize intervention strategies. Methods From March 2011 to October 2018, the project was implemented in a Tianjin (China) bathhouse, and 5165 MSM were surveyed using snowball sampling. Factors related to HIV testing behavior were analyzed by ordinal logistic regression analysis after grouping according to testing frequency, and comprehensive analysis was performed. Results The multivariate logistic analysis showed that 6 variables including young MSM (OR = 0.67, 95% CI: 0.49-0.92, p = 0.01), low-educated MSM (OR = 0.60, 95% CI: 0.48-0.77, p < 0.0001), low HIV/AIDS knowledge (95% CI: 0.57-0.83, p < 0.0001), marital status (OR = 1.30, 95% CI: 1.07-1.57, p = 0.007), acceptance of condom promotion and distribution (OR = 14.52, 95% CI: 12.04-17.51, p < 0.0001), and frequency of condom use (p < 0.05) could link to HIV testing behaviors. Conclusions In order to achieve the 95-95-95 goal, target publicity, HIV/AIDS education and promotion of HIV self-testing kits should be carried out to encourage frequent HIV testing among MSM who are young (especially students), married to women, poorly educated and who are reluctant to always use condoms.